Invasive pulmonary aspergillosis: a rare presentation of non-Hodgkin's lymphoma. Issue 824 (June 1994) - Garcia-Gonzalez, M.; Sanroman, A. L.; Arribas, R.; Torres, G.; Cuesta, C.; Moreira, V. F.
Abstract : We describe a patient with rapidly progressive pneumonia and a high level of serum lactate dehydrogenase, in whom postmortem study revealed the presence of a diffuse, small and large-cell multicentric non-Hodgkin's lymphoma, together with an invasive pulmonary aspergillosis. Aspergillosis is rare as a presenting feature of a lymphoproliferative disease; only one previous case has been reported to the best of our knowledge. Invasive aspergillosis and lymphoma should be considered in patients presenting with pneumonia and high level of lactate dehydrogenase.